Pyogenic Lumbar Facet Joint Infection with Foot Drop - Haruka Maehara; Toshihiro Sano; Yuki Yanagawa; Kyuichi Hashimoto; Nobuaki Tadokoro (Case Reports in Orthopedics)
Pyogenic facet joint infection (PFJI) is a relatively rare spinal infection. Clinical suspicion of this condition is a key for diagnosis. We report a case of PFJI which required decompression surgery for severe neurological dysfunction. The patient was a 44-year-old woman who had a previous history of orthotic therapy for idiopathic scoliosis. The patient was admitted to our hospital with a history of two days of high fever and severe low back pain. There was no neurologic deficit, and blood tests revealed high levels of inflammatory markers. There was a slight amount of fluid that had collected at L4/5 facet joint in lumbar MRI. She was admitted for examination and treatment of fever of unknown origin and low back pain. Antibiotic treatment started the day after hospitalization since the first report of the blood culture taken upon admission tested positive to gram-positive cocci. As low back pain and fever persisted, an MRI was taken again on the fifth day of hospitalization. Repeated MRI showed fluid extension from the left facet joint to paravertebral muscles and epidural space. She was diagnosed with PFJI, and facet joint puncture was performed. At this time, it became clear that she had foot drop on the right, the contralateral side of the PFJI. She underwent irrigation, debridement, and partial laminectomy. Methicillin-sensitive Staphylococcus aureus (MSSA) was detected in blood cultures at the time of hospitalization, in the puncture fluid and tissue collected during surgery. The patient recovered completely from foot drop after the operation and a three-month course of antibiotics. As the imaging findings may be inadequate in the early stages of onset and PFJI potentially causes neurologic deficit such as foot drop, neurological findings need to be carefully observed even after hospitalization and one should reexamine the MRI if symptoms or clinical findings did not improve or were aggravated.